2015
DOI: 10.5468/ogs.2015.58.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Various anatomic locations of surgically proven endometriosis: A single-center experience

Abstract: ObjectiveTo report the various anatomic locations of surgically and pathologically proven endometriosis.MethodsPathologic reports (n=1,376) of women who underwent surgeries at a single center between April 2005 and March 2013 were retrieved from the electronic medical record system of the hospital. Pathologic reports were included after performing a search by using the key-words "endometrial cyst," "endometriotic cyst," "endometriosis," or "endometrioma." Only reports dealing with female patients were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 23 publications
3
37
0
4
Order By: Relevance
“…Other organs may also be affected, such as the liver, bowels, adrenal glands, lungs, kidneys, and brain. [4][5][6][7][8][9][10][11] Cases of endometriosis have been described in the surgical scar, cesarean section scar, episiotomy scar after vaginal delivery, or following procedures where there was contact with endometrial tissue, such as hysterotomy performed in the first midterm of pregnancy, hysterectomy, ectopic pregnancy and tubal ligation. 2,12,13 In these patients, the rate of occurrence of pelvic endometriosis is similar to that of other women, and is not regarded as a risk factor for the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Other organs may also be affected, such as the liver, bowels, adrenal glands, lungs, kidneys, and brain. [4][5][6][7][8][9][10][11] Cases of endometriosis have been described in the surgical scar, cesarean section scar, episiotomy scar after vaginal delivery, or following procedures where there was contact with endometrial tissue, such as hysterotomy performed in the first midterm of pregnancy, hysterectomy, ectopic pregnancy and tubal ligation. 2,12,13 In these patients, the rate of occurrence of pelvic endometriosis is similar to that of other women, and is not regarded as a risk factor for the disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, increasing data from the literature has shown that its occurrence in postmenopausal women is quiet possible. The most commonly seen form of endometriosis is ovarian endometriomas, also known as “chocolate cysts” [ 5 ]. Endometriomas form 27.2% of ovarian masses in women older than 40 years old, and only 4.3% of the ovarian pathologies in the sixth decade of life [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Endometriosis can take one of either three forms: superficial peritoneal implants, ovarian endometriomas, and deep infiltrating endometriosis [ 4 ]. Ovarian endometriomas were found to be the most common form of endometriosis [ 5 ]. Extra-pelvic localizations of endometriomas, such as umbilical endometriomas (Villar’s node) are not rare and could be also encountered [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other associated symptoms include pain during periods (dysmenorrhoea) and/or sexual intercourse (dyspareunia), intermenstrual bleeding and infertility [ 4 ]. The most common sites for endometriotic lesions to establish are the ovaries and pelvic peritoneum, yet endometriotic lesions are also found in other sites such as the abdominal wall, fallopian tubes (FT), bowels, bladder, cervix and vagina [ 5 ].…”
Section: Introductionmentioning
confidence: 99%